Brexit - The Consequences for Pharmaceutical Patents and Supplementary Protection Certificates - Harry Melville O'Brien; Anna Louise Hatt; James Alexander Stones (University of Huddersfield Press, 2021)
Now that the UK has left the EU, and the transition period following this departure is over, we have a clearer view on the implications of Brexit on intellectual property rights and the consequences for UK based pharmaceutical companies. Although little has changed for UK applicants wishing to obtain a European patent via the European Patent Office, the UK's withdrawal from the Unified Patent Court and Unitary Patent is a huge blow to the realisation of the long awaited Unitary Patent system. Meanwhile, breaking away from the EU has also had effects on how UK pharmaceutical companies can apply for supplementary protection certificates (SPCs), with further intricacies due to the Northern Ireland Protocol. The introduction of a new manufacturing waiver for medicinal products protected by SPCs in the UK and EU will allow pharmaceutical companies more leeway with regards to stockpiling and export provisions. Perhaps most interesting of all is how UK and EU laws will diverge over the following years, now that the UK is no longer under the jurisdiction of the Court of Justice of the European Union.